The Implementation of Inclusive Education in Indonesia for Children with Special Needs: Expectation and Reality - Mohammad Efendi (Journal of ICSAR, 2018)
Government efforts to legitimize the implementation of inclusive education for children with special needs in regular schools ranging from primary education to secondary education, the more opportunities to expand opportunities for children with special needs in order to obtain quality education services. However, good policy is not balanced with the readiness of the recommended schools to provide adequate learning facilities and resource support. As a result, there is an indication that the special needs of children’s education in inclusive schools have not received appropriate educational services based on their needs.